Internal Migration in Germany in 1990 And 2005 - Szymańska, Daniela; Środa-Murawska, Stefania; Świderska, Karolina; Adamiak, Czesław (Bulletin of Geography. Socio-economic Series, 2009)
The article seeks to answer the questions concerning the possibility of identifying regular patterns within internal migration in the towns and rural areas of the Federal Republic of Germany as well as factors contributing to regional variations in the process. The research involves 439 German counties (Kreise) and compares data on internal migration in the country in the years 1991 and 2005, i.e. from its reunification until the year 2005. The 15-year period of functioning of one reunited state has been assumed sufficient for capturing some regularities and trends.